2013
DOI: 10.1016/j.bbalip.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian alpha beta hydrolase domain (ABHD) proteins: Lipid metabolizing enzymes at the interface of cell signaling and energy metabolism

Abstract: Dysregulation of lipid metabolism underlies many chronic diseases such as obesity, diabetes, cardiovascular disease, and cancer. Therefore, understanding enzymatic mechanisms controlling lipid synthesis and degradation is imperative for successful drug discovery for these human diseases. Genes encoding α/β hydrolase fold domain (ABHD) proteins are present in virtually all reported genomes, and conserved structural motifs shared by these proteins predict common roles in lipid synthesis and degradation. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 105 publications
4
151
0
Order By: Relevance
“…CGI-58 is a member of the alpha beta hydrolase domain-containing (ABHD) family of enzymes, many of which possess a classic lipase catalytic triad [104]. However CGI-58 lacks the predicted nucleophile serine within the lipase active site, and by all accounts has no intrinsic lipase activity towards TAG or many other glycerolipid and glycerophospholipid substrates [104].…”
Section: Conclusion and Perspectives: The Continued Search For Amentioning
confidence: 99%
“…CGI-58 is a member of the alpha beta hydrolase domain-containing (ABHD) family of enzymes, many of which possess a classic lipase catalytic triad [104]. However CGI-58 lacks the predicted nucleophile serine within the lipase active site, and by all accounts has no intrinsic lipase activity towards TAG or many other glycerolipid and glycerophospholipid substrates [104].…”
Section: Conclusion and Perspectives: The Continued Search For Amentioning
confidence: 99%
“…The interaction of CGI-58 with PXA1 in plants raises the intriguing question of whether mammalian CGI-58, or perhaps one or more of the other 18 a/b hydrolase-like proteins in humans (Li et al, 2009;Lord et al, 2013), might similarly interact with peroxisomal, or perhaps mitochondrial, ABC-type transport proteins to help facilitate the breakdown and/or further metabolism of various lipid substrates. Although human CGI-58 has not been shown to physically associate with any of the peroxisomal ABC transporters, a large-scale affinity-capture study that employed the peroxisomal ABC half-transporter PMP70 as bait revealed an association with another a/b hydrolase-type protein named the mesoderm-specific transcript protein (Ewing et al, 2007).…”
Section: Potential Role(s) Of Cgi-58 Protein-protein Interactions In mentioning
confidence: 99%
“…Although there is a large amount of variability in the primary sequences, all serine hydrolases with the alpha/beta hydrolase domain share a common secondary structure organization and similar subsequent tertiary structures. 8,49 The catalytic triad consists of serine, aspartic acid, and histidine, and their location is very well conserved on specific loops within the overall structure. In ABHD6 the catalytic triad is proposed to be Ser148, Asp278, and His306, with Ser148 confirmed by mutational analysis.…”
Section: Activity-based Proteome Profiling (Abpp)mentioning
confidence: 99%
“…The serine hydrolase superfamily is one of the largest groups of structurally-related enzymes and is characterized by the presence of the alpha/beta hydrolase fold domain, which is 8 β-strands forming the core surrounded by helices and loops that connect the strands. 8 All enzymes that contain this fold have a highly conserved catalytic triad: serine, histidine, and aspartic acid. These residues can be found in ABHD6 at Ser142, as confirmed by mutational analysis 6 , His306, and Asp278.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation